ANALISIS KUALITAS PELAYANAN TERHADAP PERSEPSI PELANGGAN PADA BADAN TELEKOMUNIKASI INDONESIA KOTAMADYA TEBING TINGGI - MAJU SIREGAR (JURNAL ILMIAH MAKSITEK, 2020)
An organization or agency has different functions and roles in carrying out its duties. Precision and accuracy in carrying out the functions and roles will determine the credibility or image of the institution in the middle of the community that can be called to customers in using a service, if able to understand the needs or wishes Customers will certainly be able to build positive opinions in the Community's minds about the agency. However, if everything that is expected by the customer is not realized in real, then the level of customer confidence in the agency will decrease or even cause a customer reluctance in using the service The. So that the customer's tendency to use or not service is dependent on the perception or customer perceived view directly over the agency's treatment to him.The process of customer perception is initiated when the customer has selective attention, where this tendency arises in human beings in filtering out an information they obtain or get about using the service of an agency. Then, selective distortion is a tendency in interpreting information that is appropriate to the perception of the customer itself and used as the source of confidence or initial customer confidence in the service. The last process is selective memory, in that process customers will remember information that supports the perception and confidence of customers on a service. These three processes provide clarity on the stages of the customer's perception of perceived, used and expected. So it is the benchmark of an institution to improve the quality of its workers.